THE SPECIFIC FEATURES OF ECOTOURISM SERVICES IN ENHANCING THE EFFICIENCY OF TOURISM - Umida Sadullayevna Yuldasheva (Ecominds Press, 2025)
This article analyzes the development of tourism in Uzbekistan, with a particular focus on ecotourism and its economic, environmental, and social significance. It emphasizes the important role of ecotourism in nature conservation, increasing the incomes of local populations, and promoting sustainable tourism. Various types and conceptual approaches to ecotourism are examined based on international experience and scientific research. The article also highlights the role of innovative approaches and technological solutions in the tourism sector. Overall, the article is dedicated to the prospects for the development of ecotourism in Uzbekistan and effective ways to utilize its potential.
Keywords: Tourism, ecotourism, economic development, nature conservation, environmental sustainability, socio-economic impact, national tourism, infrastructure, innovation, investment..